Effects of copper content and pelletizing pressure on the XRD patterns of melt-quenched Bi1.6Pb0.4Sr2Can-1CunOy ceramics - Natividad, Michelle T. (Animo Repository, 2024)
The effects of varying the copper content and pelletizing pressure on the x-ray diffraction (XRD) patterns of superconducting Bi1.6Pb0.4Sr2Can-1CunOy ceramics are examined. The samples were fabricated via the melt quenched method. The copper content with n=35 had the highest percentage of high Tc peaks. The low Tc phase was predominant in all samples. There is no observable trend on the effect of varying the pelletizing pressure on both high Tc and low Tc phase of the samples.